Effect of an exercise program on risk factors of falls in elderly women = Efeito de um programa de exercícios físicos nos fatores de risco de quedas em idosas - Celita Salmaso Trelha; Camila Forlini Alves de Mira; Suellen Cristina Souza Oliveira; Ligia Maxwell Pereira; Josilainne Marcelino Dias; Jefferson Rosa Cardoso (Acta Scientiarum. Health Sciences, 2012)
The aim of this study was to verify the benefits of an exercise program on functional capacity and balance in elderly community. A longitudinal study was conducted with 11 female subjects with mean age 77 (SD = 13) years. All individuals were evaluated at the beginning and at the end of the study by ‘Berg’ Balance Scale and ‘Timed Up and Go’ Test. Initially, the participants answered a questionnaire about the socio-demographics aspects, health conditions, falls and physical activity practice. Then, the subjects were submitted to a program of exercises for balance, strengthening and stretching muscles. The results of the ‘Berg’ Scale ranged from 46 to 56 points before the intervention, and from 50 to 56, after the intervention (p = 0.01). Individuals older than 75 years old had a better improvement (p = 0.04). In the ‘Timed Up and Go’ Test the percentage of improvement was 8.2% ( = 13.1; SD= 11.7). The exercise program showed a positive effect in improving risk factors of falls in the elderly community. Objetivo deste estudo foi verificar os benefícios de um programa de exercícios físicos na capacidade funcional e equilíbrio de idosos. Foi realizado um estudo longitudinal com a participação de 11 indivíduos do gênero feminino, com idade média de 77 anos (DP = 13). Todos foram avaliados no início e final do estudo pela Escala de Equilíbrio de Berg e pelo teste Timed Up and Go. Inicialmente, as participantes responderam um questionário por meio de entrevista, que abordava aspectos sociodemográficos, condições de saúde, quedas e prática de atividade física. Na sequência, as idosas foram submetidas a um programa de exercícios de treino de equilíbrio, fortalecimento e alongamentos musculares. Os resultados da escala de Berg variaram de 46 a 56 pontos, antes da intervenção e de 50 a 56 após a intervenção (p = 0,01). Os sujeitos com mais de 75 anos tiveram melhora superior (p = 0,04). No teste Timed Up and Go o percentual de melhora foi de 8,2% ( = 13,1; DP = 11,7). O programa de exercícios desenvolvido apresentou efeito positivo na melhora dos fatores de risco de quedas em idosos.